Sobre la presencia y situación de conservación de Cyathea delgadii (Cyatheaceae) en la Argentina - Krauczuk, Ernesto R. (2014)
Information on a small population of Cyathea delgadii (Cyatheaceae) founded in Corrientes Province, Argentina, is presented. The presence of this species in our country was in doubt after raising the height of the dam Yacyretá